2013
DOI: 10.1177/2325967113504734
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Gait Analysis Following Achilles Tendon Rupture With Nonsurgical Treatment Reveals Long-Term Deficiencies in Muscle Strength and Function

Abstract: Background: Precise long-term assessment of movement and physical function following Achilles tendon rupture is required for the development and evaluation of treatment, including different regimens of physical therapy.Purpose: To assess intermediate-term (<10 years by conventional thinking) objective measures of physical function following Achilles tendon rupture treated nonsurgically and to compare these with self-reported measures of physical function.Study Design: Cross-sectional study; Level of evidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 29 publications
1
49
1
Order By: Relevance
“…An earlier midterm follow-up on nonsurgically treated patients reported a similar level of side-to-side differences, with peak passive dorsiflexion that was 7.5% (1°) larger in the injured leg after 2 to 4 years. 24 A difference of 2° may not seem clinically relevant, and the ATRS value (83.2) did indicate that this group of patients may have recovered fairly well. We did, however, observe corresponding kinetic differences that may indicate or reveal functional consequences or causes for this difference.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…An earlier midterm follow-up on nonsurgically treated patients reported a similar level of side-to-side differences, with peak passive dorsiflexion that was 7.5% (1°) larger in the injured leg after 2 to 4 years. 24 A difference of 2° may not seem clinically relevant, and the ATRS value (83.2) did indicate that this group of patients may have recovered fairly well. We did, however, observe corresponding kinetic differences that may indicate or reveal functional consequences or causes for this difference.…”
Section: Discussionmentioning
confidence: 83%
“…20 These functional deficits are reported regardless of the treatment modality for both short-term 2,15 and long-term outcomes. 16,24,26 The elongated tendon and decreased tendon stiffness may have implications for daily functional activities such as gait, running, and walking on stairs. 6,7…”
mentioning
confidence: 99%
“…Besides the age difference between the <15% group and >30% group, another limitation of this study was the lack of comparison with healthy controls. Tengman and Riad 37 reported significantly lower values in ankle biomechanics during walking in patients with ATR compared with healthy controls. Possibly, patients gradually adapt to a new way of walking after ATR and this may influence the walking pattern in both the injured and the healthy side, but it is not known whether this is the case during jogging and jumping as well.…”
Section: Discussionmentioning
confidence: 95%
“…Further, these increases in ankle stiffness may contribute to the deficits in heel-rise (Brorsson et al, 2016) and reduced peak plantarflexion torque (Rosso et al, 2015) observed in humans. The improved hindlimb loading was better than that described in previous clinical literature (Olsson et al, 2011; Tengman and Riad, 2013), potentially due to the fact that an initial period of full plantarflexion casting was used to reduce tendon lengthening. Additionally, the function assessed was voluntary and not during high dynamic loading.…”
Section: Discussionmentioning
confidence: 56%
“…Long term results of conservative management, however, remain unclear. Although modern functional conservative treatment may achieve favorable Achilles tendon total rupture scores (ATRS) and a return to pre-injury activity levels (Ecker et al, 2016; Hufner et al, 2006; Karkhanis et al, 2010; Young et al, 2014), other studies examining ankle torque, 3D gait, and muscle strength have suggested that functional deficits persist from months (Brorsson et al, 2016; Metz et al, 2009) to years (Olsson et al, 2011; Rosso et al, 2015; Tengman and Riad, 2013) post-injury. Additionally, early functional weight-bearing may be beneficial compared to non-weight-bearing rehabilitation protocols (McNair et al, 2013) and may create superior tendon material properties in the short term (Freedman et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%